Assessing Climate Change Adaptation Strategies of Rural People in Nepal - Shree, Bishista (Nepalese Journal of Development and Rural Studies, 2018)
This paper presents climate change adaptation strategies applying by the rural people living around Chedaguard Municipality ward no. 6 of Jajarkot district. Both qualitative and quantitative approaches were used in the survey and further data were obtained through focus group discussions, case study and participant observations techniques. In doing so, the fous was given to agriculture based livelihoods including forest, water resources, health sector, energy and natural land reform practices. Likewise, changing pattern of rainfall, temperature, humidity were analyzed. Existence of new diseases on agriculture, water resource dryness, forest degradation, forest fire, etc. has been explored resulting with degradation of agricultural production and productivity To adapt from the climate change of this impact, local people have been using Jeevatu, Sisnu, Titepati, Banmara, Khirro, etc. as a bio-pesticides. Similarly, people have used improved cooking stoves to protect forest and they have done plantation to overcome the water resources scarcity.